PENDAMPINGAN DALAM PENGELOLAAN INFORMASI POC FERMENTASI URINE KELINCI - Heppy Purbasari; Ilham Rochad Saputra; Mahardhika Yusack Effendi (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
This service is a continuation of his previous service, namely making labels and brands for Liquid Organic Fertilizer (POC) Rabbit Urine Fermentation and AB Mix Nutirsi at Mama Hidproponics UMKM. Labels are an effective way of marketing because they contain information that consumers need. Information that can be given to provide satisfaction to consumers, then Mama Hidproponik hopes to make information about the POC content of Rabbit Urine Fermentation by conducting laboratory testing of the quality of goods. Based on the results of laboratory tests that have been carried out, the results show that Rabbit Urine Fermentation POC has good content and is not dangerous.